PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ANDROID PADA MATA PELAJARAN INFORMATIKA TERHADAP MOTIVASI BELAJAR SISWA KELAS VII SMPN 6 CILEGON - Neneng Asnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the Merdeka Curriculum, which requires teachers to provide creative learning facilities that suit the needs and characteristics of students. However, at the research location, the use of learning media is still lacking, which affects students' learning motivation.This study aims to measure the effect of using Android-based learning media (M-informatics) on the learning motivation of seventh-grade students at SMP Negeri 6 Cilegon in the Informatics subject.Through observation and questionnaires, this study found that the use of M- informatics significantly increased students' learning motivation. The questionnaire results showed that students' motivation was in the high category after using M- informatics.Android-based learning media has proven effective in boosting students' learning motivation through various aspects, such as increasing interest, providing more interactive learning experiences, and facilitating understanding of the material.This study concludes that the use of Android-based learning media has great potential to improve the quality of learning and student motivation. Therefore, it is recommended that schools can make more use of this technology to support the learning process.